Students' Perception of Basic Reading Teaching Materials Integrated Islamic Values - Siregar, Syamsiah Depalina (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
The primary aim is to enhance reading comprehension while simultaneously instilling Islamic moral and ethical values through the learning process. A qualitative descriptive method was employed using a case study approach involving students enrolled in the Basic Reading course. Data were collected through questionnaires, in-depth interviews and classroom observations. Thematic analysis was used to identify emerging patterns and themes from the data. The findings reveal that most students have a positive perception of Basic Reading materials infused with Islamic values. They found that the integrated content not only facilitated better reading comprehension but also provided meaningful insights into Islamic teachings applicable to daily life. This study concludes that students' positive perceptions indicate significant potential for implementing Islamic value-integrated teaching materials as an effective approach to teaching Basic Reading in Islamic higher education institutions.